2010
DOI: 10.1080/13636820.2010.523479
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of self‐directed and self‐regulated learning in vocational education: a theoretical analysis and synthesis of requirements

Abstract: Workplace simulations (WPS), authentic learning environments at school, are increasingly used in vocational education. This article provides a theoretical analysis and synthesis of requirements considering learner skills, characteristics of the learning environment and the role of the teacher that influence good functioning in WPS and foster students' learning. WPS appeal to students' self-directed learning (SDL) and self-regulated learning (SRL) skills, as students are required to work and learn independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 59 publications
1
124
0
3
Order By: Relevance
“…Patterson and and Crooks (2002) stated that reflection is one of the competencies required to become a self-directed learner. Reflection on the learning process is also an important component of learning (Jossberger, Brand-Gruwel, Boshuizen, & van de Wiel, 2010). De Grave (1996) also included the reflection process at the task level of meta reasoning in his coding system.…”
Section: Self-directed Processmentioning
confidence: 99%
“…Patterson and and Crooks (2002) stated that reflection is one of the competencies required to become a self-directed learner. Reflection on the learning process is also an important component of learning (Jossberger, Brand-Gruwel, Boshuizen, & van de Wiel, 2010). De Grave (1996) also included the reflection process at the task level of meta reasoning in his coding system.…”
Section: Self-directed Processmentioning
confidence: 99%
“…Research has shown that the use of regulation prompts is an effective way to train students' SRL skills (e.g., Azevedo et al 2016;Jossberger et al 2010). At the right moments in the learning process, the development portfolio should prompt students to use the metadata to either orient themselves towards their future learning performance (prompts prior to the learning task) or evaluate their past learning performance (prompts after the learning task) and then plan the learning process.…”
Section: Promptsmentioning
confidence: 99%
“…Data extracts that best exemplified the main theme(s) were subsequently ascertained. To ensure trustworthiness, the strategies suggested by Lincoln and Guba [31] were adopted, listed in Table II.…”
Section: Factor Description Studymentioning
confidence: 99%
“…It is possible to have self-regulated learning without self-directed learning. Additionally, self-direct learning and self-regulated learning refer to both an instructional design or method and a personal characteristic [31]. Thus, an educator can implement self-directed learning as an instructional method and also develop a learner skill set (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation